The effect of environmental treatment fiber on properties of palm fiber reinforced polyester composites - A. H. N., Izza; Salmah@Selamah, Haji Ayob, Prof. Madya; Ragunathan, Santiagoo; Abdul Haqi, Ibrahim (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis on June 20th - 22nd, 2009, at MS Garden Hotel, Kuantan, Pahang, Malaysia.